2016
DOI: 10.1155/2016/9256209
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating hsa-miR-106b, hsa-miR-26a, and hsa-miR-29b in Type 2 Diabetes Mellitus with Diarrhea-Predominant Irritable Bowel Syndrome

Abstract: Background and Aims. Although the differential expression of microRNA (miRNA) genes has been identified in many diseases, little information exists concerning the miRNA expression profile in type 2 diabetes mellitus (T2DM) with diarrhea-predominant irritable bowel syndrome (D-IBS). Therefore, the specific expression of miRNAs in diabetes with D-IBS is identified in the study. Materials and Methods. 201 patients with IBS and 220 matched healthy controls were included in the study. Microarray technology and real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, elevated urinary miR-29a expression was demonstrated to be significantly correlated with albuminuria and carotid intima-media thickness in patients with T2DM (16). Circulating miR-29b in patients also increases with T2DM and diarrhea-predominant irritable bowel syndrome (17). Taken together, these data indicate the crucial role of miR-29 in IR and T2DM.…”
Section: Microrna-29a Is Involved Lipid Metabolism Dysfunction and Inmentioning
confidence: 74%
“…Furthermore, elevated urinary miR-29a expression was demonstrated to be significantly correlated with albuminuria and carotid intima-media thickness in patients with T2DM (16). Circulating miR-29b in patients also increases with T2DM and diarrhea-predominant irritable bowel syndrome (17). Taken together, these data indicate the crucial role of miR-29 in IR and T2DM.…”
Section: Microrna-29a Is Involved Lipid Metabolism Dysfunction and Inmentioning
confidence: 74%
“…Growing evidence indicates that miRNAs are involved in the pathogenesis of T2DM, resulting in increased glucagon secretion and reduced incretin response (26)(27)(28). miRNAs have been implicated in the epigenetic regulation of key metabolic, inflammatory, and antiangiogenic pathways in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the mir-218-5p, mir-98-5p, and mir-3135b with T2D and bone disease, however, has not been reported in the literature. However, overexpression of mir-29b-3p in T2D and in diarrhea-predominant irritable bowel syndrome is seen [68], and it has been shown that diabetes affects tissue expression of mir-29c-3p [69].…”
Section: Discussionmentioning
confidence: 99%